2012
DOI: 10.1002/cncr.27650
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of arsenic trioxide for first‐line treatment of elderly patients with newly diagnosed acute promyelocytic leukemia

Abstract: BACKGROUND:The prognosis of acute promyelocytic leukemia (APL) in the elderly is poorer than that of younger patients after treatment with all-trans retinoic acid plus chemotherapy, which is the current standard therapy for APL. A significantly higher mortality during consolidation therapy was found, which is mainly due to deaths from sepsis following chemotherapy-induced myelosuppression. METHODS: A total of 33 patients aged 60 years or older with de novo APL were treated with single-agent arsenic trioxide (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…The introduction of newer and less toxic agents in the treatment of APL (arsenic trioxide and gentuzumab ozogamicin) will probably improve these results [18][19][20][21], allowing a better tolerance and a stronger intensity in this particular subset of frailer patients.…”
Section: Discussionmentioning
confidence: 95%
“…The introduction of newer and less toxic agents in the treatment of APL (arsenic trioxide and gentuzumab ozogamicin) will probably improve these results [18][19][20][21], allowing a better tolerance and a stronger intensity in this particular subset of frailer patients.…”
Section: Discussionmentioning
confidence: 95%
“…Two prospective studies of ATO monotherapy for newly diagnosed APL reported 5-year event-free survival (EFS), disease-free survival (DFS), and OS rates of 69%, 80% and 67%, and 74% and 64%, respectively (31, 34). ATO-associated toxicities, mainly cytopenias, liver enzyme abnormalities, QTc prolongation, and differentiation syndrome, were generally manageable and reversible (31, 34, 35). Arsenic directly binds to the PML moiety and exhibits dose-dependent dual effects with preferential a proapoptotic effect at higher concentrations and partial differentiation at lower concentrations (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The reason might be that majority of the relapsed patients lost sensitivity to ATRA due to previous exposure, making it difficult to expect a full efficacy of the synergism between ATRA and ATO in those patients. In addition, parts of recent studies about different risks of patients were summarized in Table 3 [23], [25], [31], [37][42] to make a comparison and we found that there was no strong evidence about the recommended strategy for different risk groups. However, the addition of ATO was proved to improve the long-term survival of patients with different risks, which gave support to our present study.…”
Section: Discussionmentioning
confidence: 94%